2003
DOI: 10.1017/s0305000903005658
|View full text |Cite
|
Sign up to set email alerts
|

Constraint conflict in cluster reduction

Abstract: A B S T R A C TWhen children reduce onset clusters to singletons, a common pattern is for the least sonorous member of the adult cluster to be produced. Within OPTIMALITY THEORY (Prince & Smolensky, 1993), this pattern has been accounted for in terms of a fixed ranking of onset constraints that evaluate a segment's degree of sonority, whereby onset glides violate the highest ranked constraint, and onset stops the lowest. Not all children follow the sonority pattern, however. In this paper, we apply two fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 29 publications
(56 reference statements)
7
75
0
3
Order By: Relevance
“…The subject chose to delete the fricative (the left edge consonant) and retain the nasal, which shows a deviation from the SSP. This production was supportive evidence of Pater and Barlow's (2003) findings. The Arabic similar sequence, on the other hand, was repaired by inserting an epenthetic vowel as in [amaja] for 'you do it' and [zama:j] for /ma:l/ 'camels' (Table 2).…”
Section: Stage Onesupporting
confidence: 82%
See 3 more Smart Citations
“…The subject chose to delete the fricative (the left edge consonant) and retain the nasal, which shows a deviation from the SSP. This production was supportive evidence of Pater and Barlow's (2003) findings. The Arabic similar sequence, on the other hand, was repaired by inserting an epenthetic vowel as in [amaja] for 'you do it' and [zama:j] for /ma:l/ 'camels' (Table 2).…”
Section: Stage Onesupporting
confidence: 82%
“…Furthermore, the divergence shown in the child's production which had led to a deviation from the universal pattern was attested by Pater and Barlow (2003). Although the child's production reflected the universal scale of the preferred onset cluster in terms of the sonority of its segments to a large extent, there were cases in which his production did not reflect this universal scale.…”
Section: Stage Onementioning
confidence: 96%
See 2 more Smart Citations
“…Studies taking into account natural language data have shown that the GLA is capable of realistically modeling generalizations regarding order of acquisition and learning curves: for example, Boersma and Levelt (2000) show that a GLA learner accurately predicts the order of acquisition of syllable types in Dutch. The GLA is also able to predict that children's repair strategies in response to marked structures can change over time (McLeod et al 2001) or differ from child to child (Pater & Barlow 2003); see Magri 2012:240-41 for discussion. In addition, recent work has suggested that, with regard to certain kinds of phonotactic learning, the GLA converges on more restrictive grammars than competing alternatives (Magri 2014).…”
Section: 2mentioning
confidence: 99%